Korupsi dan Pembalikan Beban Pembuktian - Wiriadinata, Wahyu (Mahkamah Konstitusi Republik Indonesia, 2012)
This paper was intended to answer a question on the extent of the effectiveness of a reversal burden of proof as stipulated in positive (prevailing) Indonesia law, that is, as provided for in Law Number 31 of 1999 on Eradication of Corruption Crime. Then, a problem that rose next was: could the application of reversal burden of proof in proving a corruption crime case prevent or reduce or even eliminate totally corruption crimes in Indonesia? This research built on a theoretical frame of thought from Roscoe Pound, who maintains that law is a tool of social engineering. This concept was cited by Muchtar Kusumaatmadja, who adapted it to Indonesia conditions and transformed it to be law as a social engineering medium. Law should be made as a medium of reforming and resolving all problems that emerge in community, including corruption crimes. One of the things to reform is the law of proof system, that is, from a conventional proof system to a reversal system. This paper was written by a juridical-normative method, that is, by studying legislations, both contained in laws and in literature/books on legal science, particularly legislations relating to reversal burden of proof. Then, the results, in a form of juridical aspect, were written in a descriptive-analytical form. The conclusion of this research was an answer to the problems put forward above, that is: Corruption crimes have been occurring continuously till now in Indonesia. Thus, Law Number 31 of 1999, Article 37, has not been effective yet in eradicating corruption crimes. Therefore, it needs to apply a pure reversal burden of proof by avoiding the incidence of bureaucratic chaos.